Florocoenotic restriction of rare species in natural forest on Nizhnedneprovskiy sands (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
Natural forest vegetation on Nizhnedneprovski sand area is presented by azonal birch, oak, aspen, alder, poplar and willow-poplar-ash forests belonging to the three classes: Alnetea glutinosae Br.-Bl. et R.Tx. 1943 ex Westhoff et al. 1946, Salicetea purpureae Moor 1958, and Dactylo glomerati – Populetea tremulae Y.O. Vorobyov et I. Solomakha 2014. In forest vegetation Nizhnedneprovskiy sand area 27 sozophytes are present, among them 9 species are included in the Red Data Book of Ukraine, 5 in European Red List, 1 in Bern Convention list, 1 in World Red List and 12 in Red List of Kherson region. The greatest number of species is observed in birch forests (12) and lowest (7) in alder.
Keywords: rare species, forest vegetation, Nizhnedneprovski sand area.